An Evaluation on Teaching and Learning Experiences During Covid-19 Pandemic Era: A Case Study - Lailatul Maya; Muchlas Suseno (STKIP PGRI Tulungagung, 2022)
The gradual spread of Covid-19 posed a major challenge to the education landscape. This encouraged lots of researchers to investigate cases happened during the era. However, likely the study of evaluation on teaching and learning experience in a phone-infused classroom is rare. A phone-infused classroom referred to the teaching and learning activity which totally based on the utilization of a phone as the main learning platform. This study aims to expose attitudes and practices of phone-based classroom use. The data were collected from 3 English teachers and 66 students in Islamic Elementary School of Mathlaul Ulum through questionnaires and focus group discussion. The researcher analyzed the transcript and presented the result in form of qualitative descriptive analysis. Three themes emerged as the findings, the impact for pedagogical practices, merit and challenges which faced by teachers and students, and value evaluations among teachers and students. Overall, both positive and negative impacts have been emerged from the utilization of phone in teaching and learning process during pandemic era. Finally, education in the outbreak atmosphere must be considered as a joint community effort by government, teachers, parents, and schools to improve the efficacy of adversely affected teaching and learning techniques which utilized mobile phones and guarantee that students do not fall behind.